Peptide hydrogel based sponge patch for wound infection treatment - Li, Lanxin; Zhou, Yuan; Li, Peizhe; Xu, Qi; Li, Kaiyan; Hu, Hai; Bing, Wei; Zhang, Zhijun (Frontiers in Bioengineering and Biotechnology, 2022)
Dressing with the function of anti-wound infection and promoting skin repair plays an important role in medicine, beauty industry, etc. In terms of anti-wound infection, traditional dressings, such as gauze, have problems such as excessive bleeding in the process of contact or removal, and slow wound healing due to poor biological compatibility. The development of new functional and biocompatible dressings has essential application value in biomedical fields. In this study, a new type of dressing based on polypeptide functional sponge patch was constructed. The porous sponge patch is made of antimicrobial peptide and medical agarose through gel and freeze-drying technology. In vitro antibacterial experiments and small animal skin wound infection model experiments show that the porous sponge has excellent antibacterial and anti-skin infection activities, as well as the function of promoting wound healing.